EVALUASI MANAJEMEN TANGGAP DARURAT BENCANA BANJIR LAHAR DINGIN DI KAWASAN SEPANJANG SUNGAI CODE KOTA YOGYAKARTA - , Tri Budiharto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
After the eruption of Mount Merapi in 2010, millions cubic of pyroclastic materials are carried by rainwaterâs runoff flowing toward Code River of which downstream region possessing a high degree of vulnerability. In order to reduce disaster risks, a disaster management is required, which is a dynamic process. Deficient disaster management will result in hostile situation. This research is aimed to evaluate the management of the disaster emergency response of coldlava flood alongside Code River after the eruption of Merapi from 2010 to 2012, in accordance with the management theory with the functions of planning, organizing, actuating, and controling. This research used deductive evaluation-qualitative method, with the research location centered on 66 of RW alongside the Code River. The sampling technique was performed by non-probability sampling, specifically purposively and it was snowball sampling by nature. Samples of the data source on the initial stage of entering the research field were selected from key informants, derived from the local government officials, community figures, and the communities in the research area which considered possessing power and authority in social situation or the research objects on the emergency management of cold-lava flood. The findings in this study are: (1) being reviewed from the planning variable, there is an absence of the policy coverage, strategy, and the procedure which are appropriate to the needs of the management of disaster emergency response. (2) Being reviewed from organizing variables, the incidence of passing the buck to each other and overlapping duties between the organizations are still present, and there is also an absence of the suitability in the authority. (3) Being reviewed from the actuating variables, there is an absence of the leadership that is capable to direct the duties effectively and quickly. (4) Being reviewed from controlling variables, there is an absence of accuracy in each organization in carrying out its duties.